2009
DOI: 10.1063/1.3171939
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of oxygen vacancy distributions in BiFeO3 films on oxygen pressure and substrate

Abstract: The epitaxial ͑001͒-oriented 250 nm BiFeO 3 /50 nm SrRuO 3 films were deposited on DyScO 3 and SrTiO 3 substrates, respectively. Following the growth, the cooling in lower oxygen pressure results in the creation of oxygen vacancies at the surface of the BiFeO 3 film and the epitaxial strain drives these vacancies to diffuse from the film surface to the film interface. The SrTiO 3 substrate strongly absorbs oxygen vacancies from the BiFeO 3 film while the DyScO 3 substrate does not. Therefore, the depth distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 20 publications
(31 reference statements)
3
28
0
Order By: Relevance
“…Oxygen vacancies can conjugate at the PZT interface under compressive strain and finally relax strain in theory. [13][14][15][16] Most oxygen vacancies are neutral and do not produce a strong enough upward E in to pole PZT films. In addition to this, the thicker PZT epitaxial films without self-poling trait were annealed at 600…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen vacancies can conjugate at the PZT interface under compressive strain and finally relax strain in theory. [13][14][15][16] Most oxygen vacancies are neutral and do not produce a strong enough upward E in to pole PZT films. In addition to this, the thicker PZT epitaxial films without self-poling trait were annealed at 600…”
Section: Resultsmentioning
confidence: 99%
“…The key difference is therefore the overall higher initial population of oxygen vacancies, determined by the choice of substrate. 22 As schematically shown in Fig. 4(b), this higher population of oxygen vacancies in as-grown PZT STO allows the formation of a domain wall conducting channel through the film.…”
Section: )O 3 Thin Filmsmentioning
confidence: 99%
“…We note that our previous studies on perovskite ferroelectrics 20,21 showed no significant differences in the structural or the functional properties between films grown on the same substrates by the two different methods, making the choice of substrate the defining parameter in our study. We could therefore compare domain wall transport in samples with very different oxygen vacancy densities and substrate chemical properties 22 but similar high crystalline 23,24 and surface quality.…”
Section: )O 3 Thin Filmsmentioning
confidence: 99%
“…Epitaxial ferroelectric films grown on these two substrates show very different disorder as a result of the superior crystalline quality of Czochralski-grown DyScO 3 , with significantly fewer dislocations than Verneuil-grown SrTiO 3 , and of the high chemical activity of SrTiO 3 substrates during growth, leading to increased densities of oxygen vacancies [148]. Extracting domain growth dynamics from measurements of domain radius as a function of writing time in the films allows qualitatively similar creep motion to be observed in both ultrahigh vacuum and ambient conditions.…”
Section: Towards More Complex Physics At Domain Wallsmentioning
confidence: 99%